Biomimetic design of Ni Co LDH composites linked by carbon nanotubes with plant conduction tissues characteristic for hybrid supercapacitors. (10th June 2021) - Huang, Mohan; Wang, Yue; Chen, Jiangchun; He, Dawei; He, Jiaqi; Wang, Yongsheng
Highlights: A unique hierarchical structure of Ni Co LDH composites linked by CNTs was prepared. CNTs/Ni Co LDH composites exhibited excellent electrochemical performance. CNTs act like plant conduction tissues to transport electrons and ions into the interior of material and effectively enhance its stability. The hybrid supercapacitor possessed high energy density and superior cycling stability. Abstract: The instability and poor conductivity of metal-organic frameworks (MOFs) are the main factors limiting its application in supercapacitors. In this paper, inspired by the bionic concept of plant conduction tissue, a unique hierarchical structure with Ni Co layered double hydroxide linked by carbon nanotubes (CNTs/Ni Co LDH) was designed and synthesized for the first time. Among them, the introduction of CNTs can not only transport electrons and ions into the interior of materials, but also can play a role in the connection when the materials break, just like lotus root silk. Furthermore, the phase transition from MOF to LDH can enhance the redox activity of the materials and thus improve the coulomb efficiency. When used as an electrode material, CNTs/Ni Co LDH composites had a superior specific capacitance of 1628 F g −1 at 1 A g −1, and had an enhanced rate capability. The assembled hybrid supercapacitor exhibited a competitive energy density of 38.89 Wh kg −1 at power density of 800 W kg −1, and had a remarkable cyclic stability with a specific capacitance retention of 99.379% for 10, 000 cycles at 5 A g −1 . This bionic concept of plant conducting tissues can provide a new way to optimize the electrochemical performance of pure MOFs or metal hydroxide materials. Graphical abstract: Image, graphical abstract